Chunks, pauses, and holistic processing in Mandarin spontaneous speech - Xie, Dongyue; Chen, Hua; Li, Bin (Frontiers in Psychology, 2023)
Chunks are multiword sequences with independent meaning and function, or formulaic based on the intuition of native speakers, hypothesized to be holistically restored and retrieved in the mental lexicon. Previous studies suggest that pauses and intonational boundaries tend to occur at the boundaries of chunks, but less discussion was made on the influence of chunk categories over mental processing and on pause placement associated with intonational continuity. This study adopted spontaneous monologues of Mandarin natives in formal and informal settings. It examined the co-occurrence of chunks and pause-defined processing units and pause placement around chunks to explore to what extent chunks are holistically processed. The results showed that Mandarin chunks were likely to be situated within a single processing unit, indicating chunks as smaller units than processing units in spontaneous speech. Major chunk categories exhibited significantly different patterns in co-occurring with processing units, indicating the influence of chunk properties on the mental processing of chunks. In addition, chunks tended to be fluently processed in spontaneous speech production as fewer hesitations occurred before and during chunk production. Major chunk categories shared a similar threshold in encountering hesitations before chunk production and differed significantly in hesitation distribution during chunk production. Hesitations in the middle of chunks were more likely to be situated within intonation units compared to those before chunk production. Speakers’ effort to maintain the intonational continuity of chunks when they encounter processing difficulties reveals the mental reality of the holistic nature of chunks. Furthermore, the co-occurrence of chunks and processing units differed significantly between the formal and informal speech genres, indicating genre influence on the mental processing of chunks. Altogether, the findings of this study have provided implications for theories on chunks and the syntactic-prosody interface and contributed to implications for the design of Mandarin instructions and teaching.